(±)-Equol interferes with the secretion of gonadotropin-releasing hormone and the expression of neuromodulators in murine neurons. Issue 1 (2nd January 2022) - Xiong, Jingyuan; Wang, Minghui; Tian, Ye; Ling, Aru; Shan, Shufang; Zhao, Li; Cheng, Guo
Abstract: S-Equol is an intestinal bacterial metabolite of the isoflavone daidzein. Racemic (± )-equol is used as a dietary estrogen supplement in menopausal women and is suggested to affect the female reproductive function and development, primarily controlled by the hypothalamic-pituitary-gonadal axis and gonadotropin-releasing hormone release. In this study, murine neurons were utilized to evaluate the effect and mechanism of (± )-equol on the secretion of gonadotropin-releasing hormone. The cells were treated with up to 20 µmol/L of (± )-equol to determine the influence on cell viability. Enzyme-linked immunosorbent assay, real-time quantitative polymerase chain reaction, and Western-blotting analysis were used to investigate the impacts of (± )-equol on the secretion and transcription of gonadotropin-releasing hormone, and the transcription and translation of key neuromodulators. This study showed that (± )-equol could decrease cell viability, increase the ability to secrete gonadotropin-releasing hormone, and interfere with the expression of neurokinin B receptor, makorin ring finger protein 3, and silent information regulator 1.